Rolling contact fatigue detection using eddy current pulsed thermography - Jianping Peng; Guiyun Tian; Li Wang; Xiaorong Gao; Yu Zhang; Zeyong Wang (2014 IEEE Far East Forum on Nondestructive Evaluation/Testing, 2014)
Rolling contact fatigue (RCF) has become a pervasive and insidious problem on all types of railway system, especially a safety challenge for high speed railway. This paper introduces eddy current pulsed thermography (ECPT), a non-destructive testing and Evaluation (NDT&E) technique, for RCF detection and characterization in rail. The theory and simulation for RCF detection using ECPT are described, and then an experimental system is introduced in detail. Different types and orientation of induction coils are employed in ECPT system for rail. The multiple cracks are analyzed in time-spatial domain from the transient thermal images. The results show that ECPT can be adapted for detection and characterization of RCF by the transient heating patterns.